Usability Level Evaluation of Village Innovation Applications Using System Usability Scale - Wardhana, Ariq Cahya; Kartiko, Condro; Saputra, Wahyu Andi (Operations Research: International Conference Series, 2022)
Usability is one of the important factors in an application. Village  Innovation Application is a  Knowledge Management System  (KMS)  that provides services to help village managers share innovation management knowledge with other villages.   To that end, the study proposes evaluating the level of useability of applications using the System Usability Scale to see the feasibility of the applications provided for use. The usability scale system has ten statements as an evaluation instrument and three assessment indicators, namely acceptability, grade scale, and adjective rating. Each statement becomes an indicator to see the level of usefulness of the application.  Evaluation of usability Application Innovation village using the System Usability Scale method can be drawn to the conclusion that the village Innovation application is categorized as meeting usability standards evidenced by the value of usability to aspects of acceptability, grade scale, and adjective rating with a final value of 68.3 meaning that the application can already be used directly by village devices